Estudo de uma topologia CA-CC trifásica de único estágio em alta frequência com correção de fator de potência e baixo flicker para leds de potência - Miranda, Pedro Henrique Almeida (2021)
The purpose of this work is a study about high-power LEDs supply through the electrical network. First, this thesis presents a review of the main international and national standards and regulations on drivers for LEDs. Next, a bibliographic review on single-phase and three-phase drivers for LED luminaires is presented, highlighting the characteristics necessary for a driver for high-power LEDs. This thesis aims to investigate different three-phase AC-DC drivers for power LEDs, in commercial and industrial installations, and to analyze possible three-phase topologies previously proposed in the literature that can be applied to power LEDs, aiming at a low implementation cost. The application of a three-phase power supply for power LEDs becomes interesting, considering that the voltage ripple in three-phase rectifiers is reduced, which allows the reduction of the filter capacitor and makes it possible not to use electrolytic capacitors. In addition, the output voltage frequency is six times higher than the mains voltage frequency. Considering the 60 Hz mains voltage frequency, flicker occurs at 360 Hz, and the percentage flicker should be limited to 29% to operate in a low-risk region. Here it is important to highlight that the focus is to use these three-phase drivers in installations where the threephase network is easily accessible. From the study carried out, it was possible to propose a three-phase AC-DC converter with a resonant switched capacitor for power LEDs with a reduced number of controlled switches and low cost. A detailed design methodology is presented, being applied to a 220W LED luminaire, which is a typical power used in public lighting. The experimental results show that it is possible to achieve a high power factor (0.99), good efficiency (89%), and reduced flicker. In conclusion, the main contribution of this thesis consists in the presentation of three-phase controller topologies for high power LEDs, which can be used in public lighting, with long service life and reduced flicker. Thus, it was possible to demonstrate that the use of the three-phase network for high power LEDs is totally viable and becomes yet another range of possibilities for driving high power LEDs.